Efek Ekstrak Kulit Pisang Kepok Terhadap Kadar Kolestrol LDL Tikus Putih Jantan Galur Wistar yang diinduksi Diet Tinggi Lemak - ERIC HARTONO (HANG TUAH MEDICAL JOURNAL, 2019)
Abstract Background: Obese people can experience dyslipidemia which is a disorder of lipid metabolism characterized by an increase or decrease in lipid fraction in the plasma. This condition if left unchecked can lead to atherosclerotic plaques which later lead to coronary heart disease. Control of dyslipidemia can be done by consuming foods that contain antioxidants. Method: Using 24 male Wistar rats, divided into 3 groups. The first group of rats fed with standard food, the second group of rats was given fat diet orally, and the third group of rats was given kepok banana skin extract and fat diet orally. At the end of experiment all animals were sacrificed and LDL levels were measured on the 30th day. Result: There was also signifficant difference (p = 0,011) of LDL levels between group of rats fed with high dose fat diet and group of rats fed with high dose fat diet and kepok banana skin extract. Conclussion: kepok banana skin extract decreased significantly the LDL levels because its flavonoid, saponin, and tanin which act as anti oxidant.